1994
DOI: 10.1063/1.356933
|View full text |Cite
|
Sign up to set email alerts
|

In situ magnetic and structural analysis of epitaxial Ni80Fe20 thin films for spin-valve heterostructures

Abstract: We have investigated structural and magnetic properties of epitaxial (100) N&Feel0 films grown on relaxed Cu/Si(lOO) seed layers. The crystallographic texture and orientation of these films was analyzed in situ by reflection high energy electron diffraction (RHEED), and M situ by x-ray diffraction and cross-sectional transmission electron microscopy (XTEM). In particular, RHEED intensities were recorded during epitaxial growth, and intensity profiles across Bragg rods were used to calculate the surface lattice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…induced uniaxial anisotropy. Single crystal Py films have been deposited epitaxially by numerous techniques, including thermal evaporation, 7,9,10 electron beam evaporation, 11 molecular beam epitaxy (MBE), [12][13][14] ion beam sputtering, 15,16 a) Electronic mail: mkk4@hi.is b) Electronic mail: tumi@hi.is c) Electronic mail: sthi@hi.is rf magnetron sputtering, 17,18 dc magnetron sputtering, 19 and pulsed laser deposition. 20 Most of these deposition methods have resulted in a single crystal Py (001) film on MgO (001) with biaxial anisotropy in the plane, and the easy directions being [110] or [100].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…induced uniaxial anisotropy. Single crystal Py films have been deposited epitaxially by numerous techniques, including thermal evaporation, 7,9,10 electron beam evaporation, 11 molecular beam epitaxy (MBE), [12][13][14] ion beam sputtering, 15,16 a) Electronic mail: mkk4@hi.is b) Electronic mail: tumi@hi.is c) Electronic mail: sthi@hi.is rf magnetron sputtering, 17,18 dc magnetron sputtering, 19 and pulsed laser deposition. 20 Most of these deposition methods have resulted in a single crystal Py (001) film on MgO (001) with biaxial anisotropy in the plane, and the easy directions being [110] or [100].…”
Section: Introductionmentioning
confidence: 99%
“…3,[21][22][23] Several groups have shown that an increase in atomic order results in deterioration of the anisotropy constant K 1 . 3,22,24,25 Uniaxial anisotropy can be induced in single crystal Py by applying an in-situ magnetic field during deposition, 7,15,16 or by post annealing 26 in magnetic field. It has been shown that magnetic field induced anisotropy strongly depends on the crystal orientation of the Py for both deposition and annealing in a magnetic field 7,27 i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, epitaxial growth appeared at the interface between the Mn-Ir grain and the Ni-Fe grain, which was confirmed by the observation of continuous lattice fringes across the interface and XRD results. An important value that characterizes epitaxy is the lattice misfit, f, of the equation defined as f=(a(A)-a(B))/a(B) where a(A) and a(B) refer to unstrained lattice constants of overlayer B and substrate A [8]. Generally, a misfit value f of (0.1) between the lattice constants for A and B and the same crystal structure are demanded for the epitaxial growth between the A layer and the B layer [9].…”
Section: Results and Dicussionmentioning
confidence: 99%
“…The film thickness, below which the ultrathin limit is defined, can be obtained from anisotropy terms [28][29][30][31][32][33]. In the case of the N i80 Fe 20 alloy, an ultrathin limit thickness of 5 nm, at room temperature (RT), was calculated using its magnetic anisotropy parameters [34][35][36].…”
Section: Introductionmentioning
confidence: 99%